Sustained intra-articular reactive oxygen species scavenging and alleviation of osteoarthritis by biocompatible amino-modified tantalum nanoparticles - Jiang, Yunsheng; Li, Tao; Yang, Junjun; Wang, Xin; Song, Xiongbo; Chen, Guangxing; Dai, Gang; Li, Rong; Yao, Chunyan; Chen, Jiajia; Chen, Cheng; Gong, Xiaoyuan; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Recent studies highlight the vital role of oxidative stress and reactive oxygen species (ROS) during progression of osteoarthritis (OA). Attenuating oxidative stress and reducing ROS generation in joints represent reasonable strategies for the treatment of OA. To address the potential question for clinical translation, and improve the biocompatibility and long-term performance of current antioxidants, the present study provided high biocompatible small positively charged tantalum nanoparticles (Ta-NH2 NPs) with sustained intra-articular catalase activity and first applied to OA intervention. Our in vitro results showed that Ta-NH2 NPs were stable with good biocompatibility, and protected viability and hyaline-like phenotype in H2O2-challenged chondrocytes. In addition, the in vivo biodistribution data demonstrated a sustained retention of Ta-NH2 NPs in the joint cavity, particularly in articular cartilage without organ toxicity and abnormality in hemogram or blood biochemistry indexes. Finally, compared with catalase (CAT), Ta-NH2 NPs exhibited long-term therapeutic effect in monosodium iodoacetate (MIA) induced OA model. This study preliminarily explored the potential of simply modified metal NPs as effective ROS scavenging agent for OA intervention, and offered a novel strategy to achieve sustained ROS suppression using biocompatible Ta-based nano-medicine in oxidative stress related diseases.